Shallow-water Sponges from a High-sedimentation Estuarine Bay (Brunei, Northwest Borneo, Southeast Asia) - Edwin Setiawan; David Relex; David J. Marshall (Universitas Gadjah Mada, 2021)
Tropical estuaries are important habitats for invertebrates including sponges, a group of marine organisms that fulfill significant ecological roles and provide ecosystem services. Here, we describe the sponge fauna from Pulau Bedukang, a small island in a turbid, variable salinity, acidified and eutrophic estuarine bay (Brunei Darussalam, northwest Borneo). We present records for 14 morphological species (OTUs). Six of these species belong to the Haplosclerida, an order of shallow-water sponges that usually tolerate more variable and extreme physical conditions. Our baseline data contribute to the regional biogeography of sponges and present a reference source for ecological studies on marine animals inhabiting variable estuarine environments. This is the first known record of sponges from the northwest Bornean region of the South China Sea that are not associated with a coral ecosystem; other studies have concerned Singapore, peninsular Malaysia, Thailand, Cambodia, Vietnam, southern China, and Taiwan.